2021 Presidential Address: Meeting Our Moment - Roberson, Quinetta M. (Academy of Management Review, 2022)
As the lead officer on the Academy of Management?s board of governors, which is accountable for conducting the organization?s activities in a manner that ensures accomplishment of its mission and objectives, the president has a range of duties and responsibilities. Because one of the most daunting of these responsibilities is to deliver a presidential address to the membership at the annual meeting, many in this role often begin ruminating over and preparing for their address well before it is necessary to do so. While I was no different in this regard, increasing disruption to key aspects of our profession, including the ways in which we engage in knowledge creation, dissemination, and application, suggested to me that a unique approach might be warranted. Accordingly, this address describes a qualitative analysis of Academy of Management presidential addresses over the past 25 years and directions for our future work as a community of scholars to engage our collective potential and leverage the disruption in order to advance management and organization science, improve work organizations, and inspire a better world.